Dependence of operational parameters of laccase-based biosensors on structure of photocross-linked polymers as holding matrixes. (June 2019) - Kavetskyy, Taras; Smutok, Oleh; Demkiv, Olha; Kasetaite, Sigita; Ostrauskaite, Jolita; Švajdlenková, Helena; Šauša, Ondrej; Zubrytska, Khrystyna; Hoivanovych, Nataliia; Gonchar, Mykhailo
Graphical abstract: Highlights: Biosensors based on laccase immobilized by photocross-linked polymers were developed. The network properties of the polymers were studied using swelling and PALS analysis. The operational parameters of the amperometric enzyme biosensors were characterized. A dependence of biosensors parameters on the structure of polymers was established. Abstract: Laccase-based amperometric enzyme biosensors of the third generation for analysis of phenol derivates have been constructed using graphite rods (type RW001) as working electrodes and the photocross-linked polymers as a matrix. Such matrix consisted of epoxidized linseed oil (ELO), bisphenol A diglycidyl ether (RD) as reactive diluent and 50% mixture of triarylsulfonium hexafluorophosphate in propylene carbonate (PI) as photoinitiator. The synthesis was made by the reaction of ELO and 10 mol.% or 30 mol.% of RD, using 3 mol.% of PI (ELO/10RD and ELO/30RD, respectively). The holding matrixes were used for an immobilization of commercial laccase from the fungus Trametes versicolor . The network properties of the polymer matrixes, holding biosensing element, were studied by means of swelling and positron annihilation lifetime spectroscopy measurements. The amperometric enzyme biosensor parameters were evaluated using cyclic voltamperometry and chronoamperometric analysis. A correlation between the constructed biosensor parameters and microscopical free volume of the biosensor holding matrixes was established.